Specific absorption rate reduction of multi‐standard mobile antenna with double‐negative metamaterial. Issue 13 (10th June 2015) - Alam, T.; Faruque, M.R.I.; Islam, M.T.
Abstract : A printed multi‐standard mobile wireless antenna loaded with double‐negative metamaterial that achieves an impedance bandwidth of 2.29 GHz (1.66 to 3.95 GHz) and 1.28 GHz (4.45 to 5.73 GHz) is presented. The proposed antenna can operate in the frequency bands of GSM (1800, 1900, 2100), WiMAX (3.2–3.6 GHZ), WLAN, Bluetooth (2.4 GHz) and WLAN (5.47–5.9 GHz). The antenna is assimilated with a semi‐circular shape radiating patch, a metamaterial loaded ground plane and a 50 Ω microstrip feed line. The antenna exhibits a planar structure and occupies a very small space of 37 × 47 × 0.8 mm 3, making it suitable for mobile wireless applications. The perceptible novelties exhibited in this proposed antenna is reduction of electromagnetic absorption with the metamaterial loaded ground plane. The proposed metamaterial antenna achieved 66.47 and 66.52% of 10 g specific absorption reduction at 1.8 and 2.4 GHz, respectively.